Kape Cat a feasibility study on establishing a civet coffee processing facility - Arano, Keith April G.; Borden, Honey Rose N.; Caliguia, Renz Jerome M.; Dimaunahan, Joan Cecile P. (College of Engineering, University of the Philippines Diliman, 2009)
This project evaluates the feasibility of establishing a civet coffee processing facility in the Philippines with a civet cat farm orchard. The product shall be referred to as "Kape Cat". It conveys a perky, fun image to the customer, ensuring them that the beans underwent meticulous cleaning, they are safe to consume, and no animals were harmed in the production of the product. Kape Cat is a beverage made from coffee beans excreted by the civet cat (locally known as "musang" and "alamid" in Southern Tagalog, "mutit" in the Cordillera region). Coffee connoisseurs are in praise with the rich, indescribable taste of the civet coffee; as compared with the "conventional" gourmet counterparts. There is a huge opportunity for Kape Cat to fill the gap made by the lack of supply of civet coffee beans. In 2011 alone, Kape Cat can capture a maximum market share of almost 38%. The results of the market analysis shows that demand is significantly higher than supply, demand-supply gap went as high as 984 kilos in year 2008. Given this large gap between demand and supply, any amount supplied can easily be absorbed. Exposure of Kape Cat will be maximized if it will be sold at high-class specialty shops and restaurants in Regions Ill, IV-A, & NCR - the top tourist, commercial and leisure spot in the Philippines. Kape Cat will be produced from a coffee processing facility in Nasugbu, Batangas, which is to be placed adjacent to a civet orchard. The orchard will be housed with civet cats and planted with coffee trees to generate the raw civet coffee beans. Other fruit-bearing trees will also be planted in the orchard to complete the dietary requirements of the civet cats and to emulate their natural habitat in the wild. In the Process Selection portion, it was determined that having an "in-house" roasting machine would benefit the company than having it subcontracted. The biomass-fired coffee roasting machine produced by DOST=ITDI will be chosen. The financial study showed an increasing trend in profitability ratios, from 1.79% to 21.28% ROA, decreasing debt-equltv, from 1.18 to 0.1577, payback period of 3.41 years, net present value of almost Phpl.5 million, and an IRR of 29.1959%. These indicators show that Kape Cat makes a favorable investment. The project also shows a positive overall contribution to the Philippine economy. The project is therefore feasible.